2012
DOI: 10.1007/s10295-012-1169-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-fermentation of xylose and cellobiose by an engineered Saccharomyces cerevisiae

Abstract: We have integrated and coordinately expressed in Saccharomyces cerevisiae a xylose isomerase and cellobiose phosphorylase from Ruminococcus flavefaciens that enables fermentation of glucose, xylose, and cellobiose under completely anaerobic conditions. The native xylose isomerase was active in cell-free extracts from yeast transformants containing a single integrated copy of the gene. We improved the activity of the enzyme and its affinity for xylose by modifications to the 5'-end of the gene, site-directed mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…The first structural determination of the enzyme was reported in Cellvibrio gilvus (Hidaka et al 2006), which was the second structural determination in GH94 after that of N,N'-diacetylchitobiose phosphorylase (Hidaka et al 2004). Cellobiose phosphorylases are often used to increase the efficiency of the fermentation of cellulosic biomass by Saccharomyces caused by intracellular expression of the gene (Aeling et al 2012;Ha et al 2013;Chomvong et al 2014). These enzymes are also used in the production of amylose from cellulosic materials by the concerted action of glycogen phosphorylase (Ohdan et al 2007;You et al 2013).…”
Section: Phosphorylases In Gh94mentioning
confidence: 99%
“…The first structural determination of the enzyme was reported in Cellvibrio gilvus (Hidaka et al 2006), which was the second structural determination in GH94 after that of N,N'-diacetylchitobiose phosphorylase (Hidaka et al 2004). Cellobiose phosphorylases are often used to increase the efficiency of the fermentation of cellulosic biomass by Saccharomyces caused by intracellular expression of the gene (Aeling et al 2012;Ha et al 2013;Chomvong et al 2014). These enzymes are also used in the production of amylose from cellulosic materials by the concerted action of glycogen phosphorylase (Ohdan et al 2007;You et al 2013).…”
Section: Phosphorylases In Gh94mentioning
confidence: 99%
“…The presence of cellobiose and xylose in hydrolysates of lignocellulosic biomass is not disadvantageous because these sugars may be converted by various microorganisms to value added products, including bioethanol. In contrast to wild-type Saccharomyces cerevisiae strains that cannot produce ethanol from xylose and cellobiose, the engineered strains coferment these sugars (Aeling et al 2012;Hawkins et al 2013). In general, the sugar profiles of the hydrolysates obtained in this study, particularly the high glucose level, enable their application as sugar feedstocks in fermentation processes.…”
Section: Enzymatic Hydrolysis Of Cellulosic Pulpsmentioning
confidence: 99%
“…In addition, in this study it was reported that heterologous expression of C. stercorarium genes encoding cellobiose phosphorylase (cepA) and LAC12 increased yeast ability to grow on cellobiose (Sadie et al, 2011). Aeling et al (2012) reported that the recombinant S. cerevisiae strain expressing the R. flavefaciens genes encoding xylose isomerase and cellobiose phosphorylase could uptake and assimilate glucose, xylose, and cellobiose under anaerobic conditions (de Haan et al, 2013). Sakamoto et al (2012) developed a recombinant S. cerevisiae strain codisplaying three types of hemicellulolytic enzymes, including endoxylanase from T. reesei, β-xylosidase from A. oryzae, and β-glucosidase from A. aculeatus on the cell-surface.…”
Section: -Engineering For Pentose Fermentation By S Cerevisiaementioning
confidence: 90%